Answer:multiply by y
Step-by-step explanation:
Mathematical Work:
f(x)=x+8
g(x)=x2-6x-7
f(g(2))=(2^2-6(2)-7)+8
f(g(2))=(4-12-7)+8
f(g(2))=-7
Explanation:
f(x)=x+8
g(x)=x2-6x-7
f(g(2))=?
2 was given as the x for function g and when you substitute 2 into function g's equation(g(2)=(2^2-6(2)-7)=-15, you would get -15. The answer to function g would be the x for function f. Which would be f(-15)=-15+8 and the answer for f(g(2)) is -7.
Answer:
22x^2-20x+21
Step-by-step explanation:
thats if you meant x^2-10x+21x^2-21
Answer:
Step-by-step explanation:
We have given:
x^4-2/x+1
Put x+1 = 0
x= 0-1
x= -1
-1 | 1 0 0 0 -2
| -1 1 -1 1
_______________
1 -1 1 -1 -1
Thus it makes the expression:
x^3-x^2+x-1 - 1/x+1
You can further confirm this expression by solving the expression:
(x4 − 2) ÷ (x + 1).
x^4 - 1 -1/x+1
x^4-1/x+1 - 1/x+1
(x^2-1) (x^2+1)/x+1 - 1/x+1
(x-1)(x+1) (x^2+1)/x+1 - 1/x+1
x+1 n the numerator will be cancelled out by x+1 in the denominator.
(x-1) (x^2+1) - 1/x+1
Multiply (x^2+1) by x-1
x(x^2+1) -1(x^2+1) - 1/x+1
x^3+x-x^2-1 - 1/x+1
x^3-x^2+x-1 - 1/x+1 ....
<h3>
Answer: 2x^2 - x - 3</h3>
====================================
Work Shown:
(x+1)(2x-3)
y(2x-3)
2xy - 3y
2x( y ) - 3( y )
2x( x+1 ) - 3( x+1 )
2x^2+2x - 3x-3
2x^2 - x - 3
Explanation:
In the second step, I replaced all of (x+1) with y. Afterward, I distributed that y term through. A few steps later, I replaced y with x+1 to help finish up the distributions. You could use the FOIL rule as an alternative approach.